Folk Cosmetics or the Search for Beauty in the Lives of Women from Merkinė (Attempt at an Ethnological Research) - Čaplikaitė, Modesta (Tautosakos darbai, 2019)
This publication presents the first attempt at conducting an ethnological research by the graduate student from Merkinė Gymnasium (Varėna district) Modesta Čaplikaitė. In the course of 2018–2019, employing a questionnaire devised with the help of her teacher Rita Černiauskienė, the student recorded detailed accounts from ten women aged between 70 and 83 and living in Merkinė parish (southern Lithuania), regarding the actual means of cosmetics and hygiene and ways of nurturing their beauty that they had used in their youth. The informants answered questions regarding the kinds of cosmetics that they used, the plants that served for making natural means of treatment for face and hair, and the predominant attitude towards female health and beauty in Lithuania during 1930s and 1940s, etc. Various popular beliefs related to this area and fragments of women’s life stories were recorded as well. The author discussed all the collected data in relation to the research works from this field. The publication is based on the study by M. Čaplikaitė under the similar title, which won the first prize in ethnology at the competition for the young philologists of Lithuania in 2019.